Yersinia pestis Interacts With SIGNR1 (CD209b) for Promoting Host Dissemination and Infection - Yang, Kun; He, Yingxia; Park, Chae Gyu; Kang, Young Sun; Zhang, Pei; Han, Yanping; Cui, Yujun; Bulgheresi, Silvia; Anisimov, Andrey P.; Dentovskaya, Svetlana V.; Ying, Xiaoling; Jiang, Lingyu; et al. (Frontiers in Immunology, 2019)
Yersinia pestis, a Gram-negative bacterium and the etiologic agent of plague, has evolved from Yersinia pseudotuberculosis, a cause of a mild enteric disease. However, the molecular and biological mechanisms of how Y. pseudotuberculosis evolved to such a remarkably virulent pathogen, Y. pestis, are not clear. The ability to initiate a rapid bacterial dissemination is a characteristic hallmark of Y. pestis infection. A distinguishing characteristic between the two Yersinia species is that Y. pseudotuberculosis strains possess an O-antigen of lipopolysaccharide (LPS) while Y. pestis has lost the O-antigen during evolution and therefore exposes its core LPS. In this study, we showed that Y. pestis utilizes its core LPS to interact with SIGNR1 (CD209b), a C-type lectin receptor on antigen presenting cells (APCs), leading to bacterial dissemination to lymph nodes, spleen and liver, and the initiation of a systemic infection. We therefore propose that the loss of O-antigen represents a critical step in the evolution of Y. pseudotuberculosis into Y. pestis in terms of hijacking APCs, promoting bacterial dissemination and causing the plague.